Paper containing light calcium carbonate

JP7637572B2Active Publication Date: 2025-02-28NIPPON PAPER IND CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021095762
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-08
Publication Date
2025-02-28
Estimated Expiration
2041-06-08

AI Technical Summary

Benefits of technology

【0019】 本発明によれば、軽質炭酸カルシウムを含有しながらも、強度の低下が抑制された紙を製造することができる。本発明によって優れた効果が得られる理由の詳細は明らかでないものの、共重合体の添加によって炭酸カルシウムがパルプと水素結合を形成しやすくなり、繊維間に入り込んだ炭酸カルシウムが繊維と水素結合を形成することで、炭酸カルシウム配合に伴う紙力の低下が抑制されるものと考えられる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637572000013
    Figure 0007637572000013
  • Figure 0007637572000014
    Figure 0007637572000014
  • Figure 0007637572000015
    Figure 0007637572000015
Patent Text Reader

Abstract

To provide paper capable of suppressing deterioration of paper strength while containing calcium carbonate.SOLUTION: There is provided paper that contains a copolymer comprising a specific structural unit and contains lightweight calcium carbonate.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to paper containing precipitated calcium carbonate. [Background technology]

[0002] In general, inorganic fillers are sometimes added to paper made of cellulose fibers. The fillers are added to improve optical properties, mainly whiteness and opacity, which tend to be insufficient with cellulose fibers alone. In recent years, due to growing environmental awareness and reducing production costs, efforts have been made to reduce the amount of cellulose fibers made from wood and instead increase the filler to increase the filler ratio in paper. However, when the filler is increased, while the optical properties improve, the tensile strength, tear strength, Stockigt sizing degree, etc. decrease. In general, chemicals such as paper strength enhancers and internal sizing agents are added to compensate for the decreased strength properties and sizing properties, but when the amount of chemicals used increases, not only does it increase the burden on production costs, but it also causes problems with internal contamination.

[0003] In recent years, neutral papermaking has progressed, and precipitated calcium carbonate is widely used as a filler. The reason is that it has a higher whiteness than fillers such as talc and clay, and depending on the synthesis method, the particle shape, particle size, and aggregation state can be adjusted, making it easy to control the physical properties imparted to paper. For this reason, much research has been conducted on the particle shape and particle size of precipitated calcium carbonate for use as a filler.

[0004] For example, Patent Document 1 describes a filler having an average particle size of 4.0 to 15.0 μm and a BET specific surface area of ​​5.0 to 10 m 2 It has been proposed to use precipitated calcium carbonate consisting of primary particles having needle-like and columnar shapes and / or aggregates thereof of about 1 / g.

[0005] Patent Document 2 describes paper with a filler added thereto. The filler is light calcium carbonate having a secondary particle size of 1 to 10 μm, which is formed by flocculating primary particles of spindle-shaped calcium carbonate, and has a BET specific surface area of ​​8 to 20 m.2 / g, pore volume 1.5-3.5cm 3 A precipitated calcium carbonate having a molecular weight in the range of 0.1 to 0.2 g has been proposed.

[0006] Furthermore, Patent Document 3 proposes reducing the drying load during paper production by using rosette-type calcium carbonate, which is made by agglomerating primary particles of spindle-shaped calcium carbonate into a burr-like shape, in combination with talc as a filler. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2013-60692 A [Patent Document 2] International Publication No. WO2004 / 108597 [Patent Document 3] JP 2012-172287 A Summary of the Invention [Problem to be solved by the invention]

[0008] The calcium carbonate described in Patent Document 1 has primary particles that are needle-like or columnar in shape. Due to the nature of this shape, when added to paper, the tips of the primary particles of light calcium carbonate are very thin and easily penetrate into the gaps between fibers, which has the disadvantage of inhibiting the formation of interfiber bonds in the paper and weakening the interlayer strength of the paper.

[0009] In addition, the precipitated calcium carbonate of Patent Document 2 has a high aspect ratio of primary particles, and therefore has the same problems as those of Patent Document 1. In addition, the calcium carbonate of Patent Document 2 has a high specific surface area of ​​secondary particles formed by floc aggregation, and generally, when a filler with a high specific surface area is used, the amount of papermaking chemicals adsorbed on the filler surface also increases, so that in order to obtain a certain level of chemical addition effect, it is necessary to add a larger amount of chemicals compared to when a filler with a low specific surface area is used.

[0010] Furthermore, Patent Document 3 describes that the combined use of rosette type precipitated calcium carbonate and talc reduces the drying load, but does not consider the relationship between the shape of the rosette type precipitated calcium carbonate and the strength of paper.

[0011] In view of the above circumstances, an object of the present invention is to provide paper which contains precipitated calcium carbonate but which is prevented from losing strength. [Means for solving the problem]

[0012] As a result of extensive research, the present inventors have found that the above problems can be solved by using precipitated calcium carbonate together with a specific copolymer. The present invention includes, but is not limited to, the following aspects. [1] A paper containing a copolymer and precipitated calcium carbonate, the copolymer being: (a) A structural unit derived from a monomer represented by the following formula 1:

[0013] [ka]

[0014] [In the formula, R 1 represents an alkenyl group having 2 to 5 carbon atoms; A 1 O is the same or different and represents an oxyalkylene group having 2 to 18 carbon atoms; n1 is the average number of moles of the oxyalkylene group added and represents a number from 1 to 100; R 2 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms]; (b) A structural unit derived from a monomer represented by the following formula 2:

[0015] [ka]

[0016] [In the formula, R 3 , R 4 and R 5each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, m represents a number from 0 to 2, 2 O is the same or different and represents an oxyalkylene group having 2 to 18 carbon atoms, n2 is the average number of moles of the oxyalkylene group added and represents a number from 1 to 100, and X represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms; (c) A structural unit derived from a monomer represented by the following formula 3:

[0017] [ka]

[0018] [In the formula, R 6 , R 7 and R 8 are each independently a hydrogen atom, -CH3 or -(CH2)rCOOM 2 represents M 1 and M. 2 are the same or different and each represents a hydrogen atom, an alkali metal, an alkaline earth metal, an ammonium group, an alkylammonium group, or a substituted alkylammonium group, and r is an integer of 0 to 2, where -(CH2)rCOOM 2 -COOM 1 or other -(CH2)rCOOM 2 When an anhydride is formed, the group M 1 and M. 2 does not exist]; Paper containing a copolymer containing two or more of the above and precipitated calcium carbonate. [2] The paper according to [1], wherein the copolymer is a copolymer containing all of (a) to (c). [3] The paper according to [1] or [2], wherein the copolymer has an Mw of 5,000 to 60,000 and an Mw / Mn ratio of 1.0 to 3.0. [4] The paper according to any one of [1] to [3], which is an uncoated paper having an ash content of 3 to 30% by weight. [5] A method for producing paper according to any one of [1] to [4], comprising a step of making paper from a stock containing the copolymer and precipitated calcium carbonate. Effect of the Invention

[0019] According to the present invention, it is possible to produce paper that contains precipitated calcium carbonate but does not experience a decrease in strength. Although the details of why the present invention provides such excellent effects are not clear, it is believed that the addition of the copolymer makes it easier for calcium carbonate to form hydrogen bonds with pulp, and the calcium carbonate that has entered between the fibers forms hydrogen bonds with the fibers, thereby suppressing the decrease in paper strength that accompanies the incorporation of calcium carbonate. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is an electron microscope photograph of Sample 3-1 (Comparative Example). [Diagram 2] FIG. 2 is an electron microscope photograph of Sample 3-2. [Diagram 3] FIG. 3 is an electron microscope photograph of Sample 3-3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention relates to paper containing precipitated calcium carbonate and a specific copolymer. copolymer The copolymer used in the present invention contains at least two of the structural units (a) to (c) described below. The ratio of each structural unit contained in the copolymer basically coincides with the charge ratio of each structural unit when synthesizing the copolymer. In the present invention, only one type of copolymer may be contained, or two or more types may be contained.

[0022] In a preferred embodiment, the copolymer according to the present invention comprises at least two of the structural units (a) to (c), and the weight ratio of (a) / (b) / (c) is preferably 1-98 / 0-98 / 1-50, more preferably 5-90 / 5-90 / 1-50, further preferably 5-50 / 50-90 / 1-50, and most preferably 5-20 / 70-90 / 1-20, with the proviso that the sum of (a) to (c) is 100.

[0023] The weight average molecular weight Mw of the copolymer is preferably 5000 or more, more preferably 6000 or more, and even more preferably 6500 or more. The upper limit of the weight average molecular weight is preferably 60000 or less, more preferably 50000 or less, and even more preferably 30000 or less. From the viewpoint of flowability and workability, the weight average molecular weight is preferably 5000 to 60000.

[0024] The molecular weight distribution (Mw / Mn) of the copolymer is preferably 1.0 or more, more preferably 1.2 or more. The upper limit is preferably 3.0 or less, more preferably 2.5 or less. The molecular weight distribution is preferably in the range of 1.0 to 3.0, more preferably 1.2 to 3.0.

[0025] The weight average molecular weight and the like can be measured by a known method using gel permeation chromatography (GPC) in terms of polyethylene glycol. (a) A structural unit derived from a monomer represented by formula 1 It is a structural unit derived from the monomer represented by formula 1.

[0026] [ka]

[0027] Here, R 1 represents an alkenyl group having 2 to 5 carbon atoms; A 1O is the same or different and represents an oxyalkylene group having 2 to 18 carbon atoms; n1 is the average number of moles of the oxyalkylene group added and represents a number from 1 to 100; R 2 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms.

[0028] In formula 1, R 1 R represents an alkenyl group having 2 to 5 carbon atoms. The number of carbon atoms in the alkenyl group is preferably 3 to 5. 1 Specific examples of the alkyl group include, but are not limited to, an allyl group, a methallyl group, and a residue of 3-methyl-3-buten-1-ol.

[0029] In formula 1, A 1 O may be the same or different and represents an oxyalkylene group having 2 to 18 carbon atoms. Examples of the oxyalkylene group include an oxyethylene group (ethylene glycol unit), an oxypropylene group (propylene glycol unit), and an oxybutylene group (butylene glycol unit), and an oxyethylene group (ethylene glycol unit) and an oxypropylene group (propylene glycol unit) are preferred.

[0030] Here, "same or different" means that A in the general formula 1 If multiple Os are included (n1 is 2 or more), each A 1 This means that the O may be the same oxyalkylene group or different (two or more types) oxyalkylene groups. 1In the case where a plurality of O's are contained, there may be mentioned a mode in which two or more oxyalkylene groups selected from the group consisting of an oxyethylene group (ethylene glycol unit), an oxypropylene group (propylene glycol unit) and an oxybutylene group (butylene glycol unit) are mixed, and it is preferable that an oxyethylene group (ethylene glycol unit) and an oxypropylene group (propylene glycol unit) are mixed, or that an oxyethylene group (ethylene glycol unit) and an oxybutylene group (butylene glycol unit) are mixed, and it is more preferable that an oxyethylene group (ethylene glycol unit) and an oxypropylene group (propylene glycol unit) are mixed. In the mode in which different oxyalkylene groups are mixed, the addition of two or more kinds of oxyalkylene groups may be block-like addition or random addition.

[0031] In formula 1, n1 is the average number of moles of oxyalkylene groups added and represents a number from 1 to 100. n1 is preferably from 1 to 50, more preferably from 5 to 50, and even more preferably from 8 to 50. The average number of moles added means the average value of the number of moles of alkylene glycol units added to 1 mole of monomer.

[0032] In formula 1, R 2 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms. If the number of carbon atoms is large, there is a risk that dispersibility will not be sufficiently exhibited when mixed with calcium carbonate. 2 is preferably a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 to 5 carbon atoms, and most preferably a hydrogen atom or a methyl group.

[0033] Examples of the monomer of formula 1 include (poly)ethylene glycol allyl ether, (poly)ethylene glycol methallyl ether, (poly)ethylene glycol 3-methyl-3-butenyl ether, (poly)ethylene (poly)propylene glycol allyl ether, (poly)ethylene (poly)propylene glycol methallyl ether, (poly)ethylene (poly)propylene glycol 3-methyl-3-butenyl ether, (poly)ethylene (poly)butylene glycol allyl ether, (poly)ethylene (poly)butylene glycol methallyl ether, (poly)ethylene (poly)butylene glycol 3-methyl-3-butenyl ether, methoxy(poly)ethylene glycol Examples of such ethers include glycol allyl ether, methoxy(poly)ethylene glycol methallyl ether, methoxy(poly)ethylene glycol 3-methyl-3-butenyl ether, methoxy(poly)ethylene (poly)propylene glycol allyl ether, methoxy(poly)ethylene (poly)propylene glycol methallyl ether, methoxy(poly)ethylene (poly)propylene glycol 3-methyl-3-butenyl ether, methoxy(poly)ethylene (poly)butylene glycol allyl ether, methoxy(poly)ethylene (poly)butylene glycol methallyl ether, and methoxy(poly)ethylene (poly)butylene glycol 3-methyl-3-butenyl ether.

[0034] As the monomer, one or more of these may be used, but it is preferable to use one or more selected from (poly)ethylene glycol (meth)allyl ether, (poly)ethylene glycol 3-methyl-3-butenyl ether, and (poly)ethylene (poly)propylene glycol allyl ether, since this can provide an excellent balance between hydrophilicity and hydrophobicity of the copolymer. In the specific examples of the monomers, the average number of moles of oxyalkylene groups (polyalkylene glycol units) added is preferably 1 to 50, more preferably 5 to 50, and even more preferably 8 to 50. In this specification, "(poly)" means that one or more of the constituent element or raw material described immediately thereafter is bonded. In this specification, "(meth)allyl" means "allyl or methallyl".

[0035] The copolymer according to the present invention may contain only one type of structural unit (a), or may contain a combination of two or more types. The monomer of formula 1 can be produced by a known method without any particular limitation, for example, a method of adding 1 to 100 moles of an alkylene oxide to an unsaturated alcohol such as allyl alcohol, methallyl alcohol, or 3-methyl-3-buten-1-ol.

[0036] (b) A structural unit derived from a monomer represented by formula 2 It is a structural unit derived from a monomer represented by formula 2.

[0037] [ka]

[0038] Here, R 3 , R 4 and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, m represents a number from 0 to 2, 2O is the same or different and represents an oxyalkylene group having 2 to 18 carbon atoms, and n2 is the average number of moles of the oxyalkylene group added and is a number from 1 to 100. X represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms.

[0039] In formula 2, R 3 , R 4 and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. In formula 2, A 2 O may be the same or different and represents an oxyalkylene group having 2 to 18 carbon atoms. Examples of the oxyalkylene group include an oxyethylene group (ethylene glycol unit), an oxypropylene group (propylene glycol unit), and an oxybutylene group (butylene glycol unit), and an oxyethylene group (ethylene glycol) and an oxypropylene group (propylene glycol) are preferred.

[0040] Here, "same or different" means that the general formula A 2 If multiple Os are included (n2 is 2 or more), each A 2 This means that the O may be the same oxyalkylene group or different (two or more types) oxyalkylene groups. 2In the case where a plurality of O's are contained, there may be mentioned a mode in which two or more oxyalkylene groups selected from the group consisting of an oxyethylene group (ethylene glycol unit), an oxypropylene group (propylene glycol unit) and an oxybutylene group (butylene glycol unit) are mixed, and it is preferable that an oxyethylene group (ethylene glycol unit) and an oxypropylene group (propylene glycol unit) are mixed, or that an oxyethylene group (ethylene glycol unit) and an oxybutylene group (butylene glycol unit) are mixed, and it is more preferable that an oxyethylene group (ethylene glycol unit) and an oxypropylene group (propylene glycol unit) are mixed. In the mode in which different oxyalkylene groups are mixed, the addition of two or more kinds of oxyalkylene groups may be block-like addition or random addition.

[0041] In formula 2, n2 is the average number of moles of oxyalkylene groups added and represents a number from 1 to 100. n2 is preferably from 1 to 50, more preferably from 5 to 50, and even more preferably from 8 to 50. The average number of moles added means the average value of the number of moles of alkylene glycol units added to 1 mole of monomer.

[0042] The copolymer may contain only one type of structural unit derived from the monomer represented by formula 2, or may contain two or more types in combination. In particular, it is preferable that the copolymer contains two types of monomers having different average added mole numbers of oxyalkylene groups, and it is more preferable that the copolymer contains a combination of a monomer having an average added mole number n2 of oxyalkylene groups of 1 and a monomer having an average added mole number n2 of oxyalkylene groups of more than 1 and 100 or less.

[0043] In a preferred embodiment, when n2 is 1, for example, a compound represented by formula 2 in which X is a hydrogen atom is included, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate, and a compound represented by formula 2 in which n2 is 1 and X is a hydrogen atom is preferred, with 2-hydroxyethyl (meth)acrylate being preferred.

[0044] When a monomer in which n2 is 1 is used in combination with a monomer in which n2 is greater than 1 and not greater than 10, the weight ratio of the two is preferably 1 / 99 to 99 / 1, more preferably 3 / 97 to 50 / 50, and even more preferably 5 / 95 to 30 / 70. This weight ratio corresponds to the weight ratio of the monomers charged when synthesizing the copolymer.

[0045] In formula 2, X represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms. When the number of carbon atoms is not too large, the additive (dispersant) for hydraulic compositions exhibits sufficient dispersibility in the hydraulic composition. Therefore, X is preferably a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 to 5 carbon atoms, and most preferably a hydrogen atom or a methyl group.

[0046] Examples of the monomer of formula 2 include esters of unsaturated monocarboxylic acids such as (meth)acrylates (hereinafter, "(meth)acrylate" means "acrylate or methacrylate") with (poly)alkylene glycols such as (poly)ethylene glycol, (poly)ethylene (poly)propylene glycol, (poly)ethylene (poly)butylene glycol, methoxy(poly)ethylene glycol, methoxy(poly)ethylene (poly)propylene glycol, and methoxy(poly)ethylene (poly)butylene glycol.

[0047] Specifically, for example, (poly)ethylene glycol (meth)acrylate, (poly)ethylene (poly)propylene glycol (meth)acrylate, (poly)ethylene (poly)butylene glycol (meth)acrylate, methoxy (poly)ethylene glycol (meth)acrylate, methoxy (poly)ethylene (poly)propylene glycol (meth)acrylate, methoxy (poly)ethylene (poly)butylene glycol (meth)acrylate, (poly)alkylene glycol (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, etc. may be mentioned. As the monomer of formula 2, one or more of these may be used in combination, but it is preferable to use (poly)alkylene glycol (meth)acrylate, and it is more preferable to use (poly)ethylene glycol (meth)acrylate, methoxy (poly)ethylene glycol (meth)acrylate. When the monomer is a (poly)alkylene glycol (meth)acrylate, the average number of moles of (poly)alkylene glycol added is preferably 1 to 50. When n2 of the monomer is 1 and the monomer is a (poly)alkylene glycol (meth)acrylate, the average number of moles of (poly)alkylene glycol added in the monomer is preferably 1. When n2 is greater than 1 and equal to or less than 10 and the monomer is a (poly)alkylene glycol (meth)acrylate, the average number of moles of (poly)alkylene glycol added in the monomer is preferably greater than 1 and equal to or less than 100, more preferably 5 to 50, and even more preferably 8 to 50.

[0048] The monomer of formula 2 can be produced by a known method without any particular limitation, for example, a method of esterifying an unsaturated monocarboxylic acid such as (meth)acrylic acid with a (poly)alkylene glycol such as (poly)ethylene glycol, (poly)ethylene (poly)propylene glycol, (poly)ethylene (poly)butylene glycol, methoxy(poly)ethylene glycol, methoxy(poly)ethylene (poly)propylene glycol, or methoxy(poly)ethylene (poly)butylene glycol.

[0049] (c) A structural unit derived from a monomer represented by formula 3 It is a structural unit derived from a monomer represented by formula 3.

[0050] [ka]

[0051] Here, R 6 , R 7 , and R 8 are each independently a hydrogen atom, -CH3, or -(CH2)rCOOM 2 represents -(CH2)rCOOM 2 -COOM 1 or other -(CH2)rCOOM 2 and an anhydride may be formed, in which case, M 1 and M 2 does not exist. 1 and M 2 are the same or different and each represents a hydrogen atom, an alkali metal, an alkaline earth metal, an ammonium group, an alkylammonium group, or a substituted alkylammonium group, and r represents an integer of 0 to 2.

[0052] Examples of the monomer of formula 3 include unsaturated monocarboxylic acid monomers and unsaturated dicarboxylic acid monomers. Examples of the unsaturated monocarboxylic acid monomers include acrylic acid, methacrylic acid, and crotonic acid, as well as their salts (e.g., monovalent metal salts, ammonium salts, and salts with organic amines). Examples of the unsaturated dicarboxylic acid monomers include maleic acid, itaconic acid, citraconic acid, and fumaric acid, as well as their salts (e.g., monovalent metal salts, ammonium salts, and salts with organic amines), and their anhydrides.

[0053] The copolymer according to the present invention may contain only one type of constitutional unit derived from the monomer of formula 3, or may contain two or more types. (Method of synthesizing copolymer) The copolymer of the present invention can be produced by copolymerizing each of the predetermined monomers by a known method, such as polymerization in a solvent or bulk polymerization.

[0054] Examples of the solvent used in the polymerization in a solvent include water; lower alcohols such as methyl alcohol, ethyl alcohol, and isopropyl alcohol; aromatic hydrocarbons such as benzene, toluene, and xylene; alicyclic or aliphatic hydrocarbons such as cyclohexane and n-hexane; esters such as ethyl acetate; and ketones such as acetone and methyl ethyl ketone. From the viewpoint of the solubility of the raw material monomers and the resulting copolymer, it is preferable to use one or more selected from the group consisting of water and lower alcohols, and among them, water is preferably used. It is more preferable that

[0055] When copolymerization is carried out in a solvent, each monomer and the polymerization initiator may be continuously added dropwise to a reaction vessel, or a mixture of each monomer and the polymerization initiator may be continuously added dropwise to a reaction vessel. Alternatively, a solvent may be charged into a reaction vessel, and a mixture of the monomers and the solvent and a polymerization initiator solution may be continuously added dropwise to the reaction vessel, or a part or all of the monomers may be charged into a reaction vessel, and the polymerization initiator may be continuously added dropwise.

[0056] The polymerization initiator that can be used for copolymerization is not particularly limited, but when copolymerization is performed in an aqueous solvent, examples of the polymerization initiator include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate; and water-soluble organic peroxides such as t-butyl hydroperoxide. In this case, accelerators such as sodium hydrogen sulfite and Mohr's salt may be used in combination. In addition, when copolymerization is performed in a solvent such as a lower alcohol, an aromatic hydrocarbon, an alicyclic or aliphatic hydrocarbon, an ester, or a ketone, for example, peroxides such as benzoyl peroxide and lauryl peroxide; hydroperoxides such as cumene peroxide; and aromatic azo compounds such as azobisisobutyronitrile may be used as polymerization initiators. In this case, accelerators such as amine compounds may be used in combination. Furthermore, when copolymerization is performed in a water-lower alcohol mixed solvent, for example, the polymerization initiators or combinations of the polymerization initiator and accelerator described above may be appropriately selected and used. The polymerization temperature varies depending on the polymerization conditions such as the solvent used and the type of polymerization initiator, but is usually performed in the range of 50 to 120°C.

[0057] In the copolymerization, a chain transfer agent may be used to adjust the molecular weight, if necessary. Examples of the chain transfer agent used include known thiol compounds such as mercaptoethanol, thioglycerol, thioglycolic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiomalic acid, octyl thioglycolate, and 2-mercaptoethanesulfonic acid; phosphorous acid, hypophosphorous acid, and salts thereof (sodium hypophosphite, potassium hypophosphite, etc.), sulfurous acid, hydrogen sulfite, dithionous acid, metabisulfite, and salts thereof (sodium sulfite, potassium sulfite, sodium hydrogen sulfite, potassium hydrogen sulfite, sodium dithionite, potassium dithionite, sodium metabisulfite, potassium metabisulfite, etc.), and lower oxides and salts thereof; and the like. These may be used alone or in combination of two or more kinds. Furthermore, in order to adjust the molecular weight of the copolymer, in addition to the above-mentioned monomers, another monomer having higher chain transferability may be used as a monomer for obtaining the copolymer. An example of a monomer having high chain transferability is a (meth)allylsulfonic acid (salt) monomer. The content of such a monomer in the copolymer is usually 20% by weight or less, and preferably 10% by weight or less.

[0058] When copolymerization is performed in an aqueous solvent to obtain a copolymer, the pH during polymerization is usually strongly acidic due to the influence of the monomer having an unsaturated bond, but this may be adjusted to an appropriate pH. If pH adjustment is required during polymerization, the pH can be adjusted using an acidic substance such as phosphoric acid, sulfuric acid, nitric acid, alkyl phosphoric acid, alkyl sulfuric acid, alkyl sulfonic acid, or (alkyl)benzenesulfonic acid. Among these acidic substances, phosphoric acid is preferably used because of its pH buffering effect. However, in order to eliminate the instability of the ester bond of the ester monomer, it is preferable to perform polymerization at a pH of 2 to 7. In addition, there is no particular limitation on the alkaline substance that can be used to adjust the pH, but alkaline substances such as NaOH and Ca(OH)2 are generally used. The pH adjustment may be performed on a solution containing the monomer before polymerization, or on a solution containing the copolymer after polymerization. In addition, a part of the alkaline substance may be added before polymerization to perform polymerization, and then the pH adjustment may be performed on the solution containing the copolymer.

[0059] Light calcium carbonate The paper of the present invention contains precipitated calcium carbonate. The precipitated calcium carbonate used in the present invention is not particularly limited as long as it is used for papermaking purposes, and for example, calcium carbonate in the shape of a needle, column, spindle, sphere, cube, rosette, etc. can be used.

[0060] The light calcium carbonate used in the present invention may be calcite-based or aragonite-based, and may be produced by any method. The average particle size of the light calcium carbonate is not particularly limited, but is preferably 0.1 to 10 μm, more preferably 0.5 to 7 μm, and further preferably 1 to 5 μm.

[0061] In the present invention, the precipitated calcium carbonate and the copolymer are used in combination. The amount of the copolymer used is preferably 0.1 to 10 parts by weight, more preferably 0.3 to 5 parts by weight, and even more preferably 0.6 to 3 parts by weight, per 100 parts by weight of the precipitated calcium carbonate.

[0062] In the present invention, the amount of light calcium carbonate used is not particularly limited. When the light calcium carbonate is used as an internal filler, the light calcium carbonate is preferably used in an amount of 10 parts by weight or more, more preferably 50 parts by weight or more, and even more preferably 70 parts by weight or more, per 100 parts by weight of the internal filler used.

[0063] The amount of calcium carbonate blended into the paper stock is preferably 2 to 30% by weight based on the pulp weight in terms of opacity, etc. The filler content in the paper (ash content in the paper) is preferably 10% by weight or more and 40% by weight or less.

[0064] Paper containing light calcium carbonate The paper of the present invention contains light calcium carbonate, yet effectively prevents the paper from losing strength, and can be used for various applications. Examples of the types of paper include various coating base papers, newsprint, high-quality and medium-quality paper, electrophotographic transfer paper, inkjet paper, thermal paper, pressure-sensitive paper, craft paper, pressure-bonded recording paper, packaging paper, paper containers, cardboard, wallpaper, fiberboard, photographic base paper, impregnated base paper, and flame-retardant paper. In one embodiment, the paper of the present invention is suitable as printing paper for use in various printing methods such as offset printing and gravure printing.

[0065] The basis weight of the paper according to the present invention is not particularly limited, but is, for example, 30 to 650 g / m 2 The thickness can be in the range of 35 to 200 g / m 2 , 40~120g / m 2 , 40~80g / m 2 The paper of the present invention may also be made into thick paper such as multi-layer paperboard or card exceeding the above range.

[0066] Pulps for papermaking raw materials include, for example, commonly used bleached chemical pulps such as LBKP and NBKP, unbleached pulps such as LUKP and NUKP, mechanical pulps such as groundwood pulp (GP), pressurized groundwood pulp (PGW), refiner groundwood pulp (RGP), and thermomechanical pulp (TMP), deinked waste paper pulp (DIP), and broke, which are appropriately mixed and used. In addition, one or more types of pulp fibers obtained from non-wood fiber raw materials such as kenaf, synthetic pulp, and inorganic fibers can be blended into the base paper. Mechanical pulp and DIP can be bleached as necessary, and the degree of bleaching can be freely selected.

[0067] The light calcium carbonate of the present invention can be used by mixing with commonly used fillers, for example, heavy calcium carbonate, light calcium carbonate other than that of the present invention, calcium sulfite, gypsum, talc, kaolin, engineered kaolin, calcined kaolin, white carbon, amorphous silica, delaminated kaolin, diatomaceous earth, magnesium carbonate, titanium dioxide, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide, papermaking sludge, inorganic particles recycled from deinking floss, etc., and organic fillers such as urea-formaldehyde resin, vinyl chloride resin, polystyrene resin, urea / formaldehyde resin, melamine resin, styrene / butadiene copolymer resin, phenol resin, plastic hollow particles, etc. The mixing ratio can be adjusted according to the quality of the paper.

[0068] If the ash content in the paper is less than 3% by weight, the optical properties of the paper, mainly whiteness and opacity, tend to be insufficient, so the ash content of the paper of the present invention is preferably 5% by weight or more, and more preferably 10% by weight or more. On the other hand, if the ash content exceeds 30% by weight, problems such as wire wear and dirt inside the papermaking machine tend to occur. Therefore, it is generally preferable to add the filler in the range of 3 to 30% by weight, and it is particularly preferable to add the filler in the range of 5 to 20% by weight.

[0069] In addition to pulp and fillers, various internal papermaking auxiliaries such as anionic, nonionic, cationic or amphoteric retention aids, drainage aids, paper strength enhancers, dyes, fluorescent dyes, bulk enhancers, etc. can be used as necessary. Specific examples of internal sizing agents include alkyl ketene dimers, alkenyl succinic anhydrides, styrene-acrylics, higher fatty acids, petroleum resin sizing agents, rosin sizing agents, etc. Specific examples of retention aids, drainage aids, and paper strength enhancers include polyvalent metal compounds such as aluminum (specifically, aluminum sulfate, aluminum chloride, sodium aluminate, basic aluminum compounds, etc.), various starches, cellulose nanofibers, cellulose derivatives such as carboxymethyl cellulose, hydroxyethyl cellulose, and methyl cellulose, polyacrylamides, urea resins, polyamide / polyamine resins, polyethyleneimines, polyamines, polyvinyl alcohol, and polyethylene oxides. The paper containing the precipitated calcium carbonate of the present invention has high chemical addition efficiency and excellent sizing properties.

[0070] When the filler containing the precipitated calcium carbonate of the present invention is added to a pulp raw material, it is preferable to add the filler while thoroughly stirring the pulp raw material. Examples of the location where the filler is added include the inlet of a machine chest and the suction port of a fan pump.

[0071] The papermaking conditions are not particularly limited, and examples of the papermaking machine include commercial-scale papermaking machines such as a fourdrinier papermaking machine, a twin-wire papermaking machine, an on-top papermaking machine, a cylinder papermaking machine, and a short wire papermaking machine, and can be appropriately selected according to the purpose. As the papermaking method, any method such as acidic papermaking, neutral papermaking, and weakly alkaline papermaking can be used, but since calcium carbonate dissolves in the acidic range, it is desirable to make the paper in the neutral to weakly alkaline range.

[0072] A surface treatment agent may be applied to the paper to improve surface strength, water resistance, and ink adhesion. The type of surface treatment agent is not particularly limited, but it is preferable to use starches such as raw starch, oxidized starch, esterified starch, cationic starch, and self-modified starch produced by thermochemical or enzymatic modification in a paper mill using acetylated tapioca starch as a raw material, and modified starches such as aldehyde starch and hydroxyethylated starch. It is also possible to use cellulose derivatives such as carboxymethyl cellulose, hydroxyethyl cellulose, methyl cellulose, and cellulose nanofiber, modified alcohols such as polyacrylamide, polyvinyl alcohol, carboxyl-modified polyvinyl alcohol, and acetoacetylated polyvinyl alcohol, styrene-butadiene copolymers, polyvinyl acetate, vinyl chloride-vinyl acetate copolymers, polyvinyl chloride, polyvinylidene chloride, and polyacrylic esters in combination. In addition, it is also possible to use surface sizing agents such as styrene-based sizing agents, olefin-based sizing agents, acrylate-based sizing agents, styrene-acrylic sizing agents, and cationic sizing agents in combination for the purpose of improving sizing properties. In the present invention, various auxiliary agents that are typically blended in a normal clear coating, such as dispersants, thickeners, water retention agents, defoamers, water resistance agents, colorants, conductive agents, etc., may be used as necessary.

[0073] As a device for applying the surface treatment coating liquid, a known size press device, such as a two-roll type, a three-roll type, a gate roll type, or a film transfer type, can be used. The film transfer type is a method in which a coating film in a wet state is formed on an applicator roll and the coating film is transferred to the surface of the base paper, and examples of such a method include a transfer roll coater and a rod metering size press coater. Coating may also be performed using a coater (applicator) such as a curtain coater, a spray coater, or a blade coater.

[0074] These coating devices apply the surface treatment coating liquid to the paper at a rate of 0.1 to 5.0 g / m per side. 2After coating, the coating can be dried and finished with a dryer, but in order to improve printability, it is preferable to treat the coating with a calender such as a machine calender, soft calender, shoe calender, etc. The surface treatment liquid may be applied to both sides.

[0075] In the present invention, a coated paper having at least one coating layer mainly composed of a pigment and an adhesive can be obtained. According to the present invention, the strength of the paper is improved, and therefore the coated paper has excellent blister resistance and good sizing properties, and therefore the coated paper has excellent surface smoothness.

[0076] In one embodiment, the coated base paper may be prepared by coating a coating liquid containing a surface treatment agent on the paper to which the above-mentioned precipitated calcium carbonate has been added. This surface treatment has the effect of improving the surface strength of the coated base paper or cleaning foreign matter on the surface of the coated base paper, thereby suppressing the occurrence of streaks, etc. However, in the case of an on-machine coater in which the coated base paper is made, and a coating layer mainly composed of a pigment and an adhesive is applied and dried, the surface treatment may be omitted in order to avoid limitations in drying capacity and the risk of paper breakage.

[0077] The coated base paper can also be subjected to a smoothing finishing treatment using a machine calender, soft calender, or the like. The pigment used in the coating layer is not particularly limited, and may be one or more of pigments used in the field of ordinary coated paper, such as heavy calcium carbonate, light calcium carbonate of the present invention or other, calcium sulfite, gypsum, talc, kaolin, engineered kaolin, calcined kaolin, white carbon, amorphous silica, delaminated kaolin, diatomaceous earth, magnesium carbonate, titanium dioxide, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide, papermaking sludge, inorganic particles recycled from deinking floss, and organic fillers such as urea-formalin resin, vinyl chloride resin, polystyrene resin, urea / formalin resin, melamine resin, styrene / butadiene copolymer resin, phenolic resin, plastic hollow particles, etc., as required. The mixing ratio can be adjusted according to the quality of the paper, and is not particularly limited.

[0078] The pigment coating liquid may contain, as an adhesive, an adhesive used in the field of ordinary coated paper, or various surface treatment agents used as surface treatment agents in the above-mentioned uncoated paper. These adhesives may be used alone or in combination of two or more kinds.

[0079] The amount of adhesive to be added is not particularly limited, but is usually 1 to 50 parts by weight, and preferably 5 to 30 parts by weight, per 100 parts by weight of the pigment. Furthermore, if necessary, various auxiliary agents such as colored dyes or colored pigments, fluorescent whitening dyes, thickeners, water retention agents, antioxidants, antiaging agents, electrical conductivity inducers, defoamers, ultraviolet absorbers, dispersants, pH adjusters, release agents, water-resistant agents, and water-repellents may be appropriately blended.

[0080] The solids concentration of the pigment coating liquid can be selected in the range of 25 to 80% by mass, and in consideration of adjustment of the coating amount and operability, a range of 50 to 70% by mass is preferable. There is no particular restriction on whether the coating layer provided on the coated base paper is one layer or two or more layers. In the case of multiple layers, they do not all need to be the same, and can be adjusted appropriately according to the required quality level. There is also no particular restriction on the amount of coating in the coating layer, and it can be adjusted according to the white paper quality and printing quality of the coated paper, but it is generally 0.5 to 40.0 g / m per side. 2 That's about it.

[0081] Regarding the coating method for providing the coating layer in the present invention, various coating devices generally used in the field of coated paper production, such as an air knife coater, various blade coaters, gate roll coaters, roll coaters, die coaters, curtain coaters, spray coaters, etc., can be used appropriately.

[0082] After the pigment coating liquid is applied to the base paper, the coating layer is dried to obtain the coated paper. The drying method can be selected from any of the usual methods, such as a steam heater, a gas heater, an infrared heater, an electric heater, a hot air heater, a microwave, a cylinder dryer, etc.

[0083] The coated paper thus obtained may be passed through any of various known and commonly used finishing devices, such as a supercalender, gloss calender, soft calender, matte calender, etc., to give it a product finish.

[0084] (Electrophotographic transfer paper) The paper of the present invention can be used to manufacture electrophotographic transfer paper. According to the present invention, electrophotographic transfer paper that is less prone to curling or paper dust during printing can be obtained. A general papermaking machine can be used, and is not particularly limited, but the papermaking machine used to manufacture electrophotographic transfer paper is preferably a hybrid former or an on-top former having a double-sided dewatering mechanism.

[0085] The pulp raw material for the electrophotographic transfer paper produced in the present invention is not particularly limited, and may be any pulp generally used as a raw material for papermaking, such as the various pulps exemplified for uncoated paper. Among them, the more deinked pulp is used, the more desirable it is from an environmental standpoint.

[0086] The light calcium carbonate of the present invention can be used alone or in combination with other papermaking fillers. When used in combination with other papermaking fillers, the known fillers exemplified in the non-coated paper can be used alone or in combination of two or more of them as appropriate. The mixing ratio can be adjusted according to the quality of the paper, and in order to reduce curling and paper dust during printing and to suppress wire wear during papermaking, it is preferable to contain 50 parts by weight or more of the specific light calcium carbonate of the present invention in 100 parts by weight of the internal filler of the paper, more preferably 60 parts by weight or more, and particularly preferably 70 parts by weight or more.

[0087] The ash content in paper is preferably 5% by weight or more, more preferably 10% by weight or more, because the optical properties of the paper, mainly whiteness and opacity, tend to be insufficient when it is less than 3% by weight. On the other hand, when the ash content exceeds 30% by weight, problems such as wire wear, dirt inside the papermaking machine system, transportability in electrophotographic printers due to reduced bending stiffness (multiple feeding, jamming troubles, etc.), and paper dust generation are likely to occur. Therefore, it is generally preferable to add it in the range of 3 to 30% by weight, and it is particularly preferable to add it in the range of 5 to 20% by weight.

[0088] When manufacturing electrophotographic transfer paper containing the light calcium carbonate of the present invention, one or more of various papermaking chemicals and auxiliaries such as those exemplified in the above-mentioned uncoated paper can be used in combination. These auxiliaries may be added in advance to the slurry of the light calcium carbonate of the present invention and then applied to the papermaking machine, or may be applied to the papermaking machine separately from the slurry of the light calcium carbonate of the present invention. In the electrophotographic transfer paper, as in the above, high chemical addition efficiency is obtained, and therefore the size expression is excellent.

[0089] For the purpose of increasing the surface strength, a surface treatment agent may be applied onto the electrophotographic electric train transfer paper to which the specific light calcium carbonate of the present invention is internally added. As the surface treatment agent, the surface treatment agents exemplified for the uncoated paper may be used. In addition, in order to control the electrical resistance and improve the toner fixing property, it is preferable to add an inorganic conductive agent such as sodium chloride, sodium sulfate, or potassium chloride as a conductive agent, or an organic conductive agent such as dimethylaminoethyl methacrylate, and apply it as an external additive. The amount of the surface treatment agent containing the conductive agent to be applied is appropriately adjusted, but the usual amount is 0.5 to 4.0 g / m on both sides. 2 The amount of conductive agent applied is about 0.02 to 0.5 g / m on both sides. 2 That's about it.

[0090] The basis weight of the electrophotographic transfer paper of the present invention is, for example, 40 to 80 g / m 2 The physical properties may be adjusted to a level having a coefficient of friction, etc., that is the same as that of ordinary electrophotographic transfer paper. The present invention will be described in detail below with reference to specific examples, but the present invention is not limited to the following examples. In this specification, unless otherwise specified, all "%" means "% by weight" and numerical ranges include their endpoints. EXAMPLES

[0091] Experiment 1: Preparation of copolymer (1) Copolymer 1 291 parts of water and 7 parts of polyethylene glycol monoallyl ether (average number of moles of ethylene oxide added: 10) were added to a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device, a nitrogen inlet tube, and a dropping device, and the atmosphere in the reaction vessel was replaced with nitrogen while stirring. After heating to 100°C under a nitrogen atmosphere, a monomer aqueous solution containing 4 parts of methacrylic acid, 0.1 parts of acrylic acid, 22 parts of methoxypolyethylene glycol methacrylate (average number of moles of ethylene oxide added: 25), 36 parts of 2-hydroxypropyl acrylate, and 33 parts of water, and a mixture of 1 part of ammonium persulfate and 44 parts of water were continuously dropped into the reaction vessel maintained at 100°C for 2 hours each. After the dropping was completed, the mixture was reacted for another hour while maintaining the temperature at 100°C, to obtain an aqueous solution of a copolymer.

[0092] The molecular weight of the copolymer was measured by GPC under the following conditions. Measuring equipment: Tosoh Columns used: Shodex Column OH-pak SB-806HQ, SB-804HQ, SB-802.5HQ Eluent: 0.05 mM sodium nitrate / acetonitrile 8 / 2 (v / v) Standard material: Polyethylene glycol (Tosoh, GL Science) Detector: Differential refractometer (Tosoh) Calibration curve: Polyethylene glycol standard (2) Copolymer 2 In a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device, a nitrogen inlet tube and a dropping device, 148 parts of water, 347 parts of polyethylene glycol monoallyl ether (average number of moles of ethylene oxide added: 10), and 1 part of a compound in which the 3- and 3-positions of 4,4'-dihydroxydiphenylsulfone are allyl-substituted were charged, and the reaction vessel was purged with nitrogen under stirring, and the temperature was raised to 100°C under a nitrogen atmosphere. Then, a monomer aqueous solution obtained by mixing 78 parts of acrylic acid, 1 part of a 31% NaOH aqueous solution, and 288 parts of water, and a mixed solution of 7 parts of ammonium persulfate and 113 parts of water were continuously dropped into the reaction vessel maintained at 100°C for 2 hours. Furthermore, the mixture was reacted for 1 hour while maintaining the temperature at 100°C, to obtain an aqueous solution of a copolymer. (3) Copolymer 3 (Comparative Example) A glass reaction vessel equipped with a thermometer, a stirrer, a reflux device, a nitrogen inlet tube, and a dropping device was charged with 198 parts of water, and the reaction vessel was replaced with nitrogen while stirring, and the temperature was raised to 100°C under a nitrogen atmosphere. Then, an aqueous monomer solution obtained by mixing 72 parts of acrylic acid, 70 parts of a 31% NaOH aqueous solution, and 54 parts of water, and a mixed solution of 4 parts of ammonium persulfate and 37 parts of water were each continuously dropped into the reaction vessel maintained at 100°C over a period of 2 hours. Furthermore, the mixture was reacted for 1 hour while maintaining the temperature at 100°C, to obtain an aqueous copolymer solution.

[0093] [Table 1]

[0094] Experiment 2: Production and evaluation of calcium carbonate-loaded paper A pulp slurry consisting of 100% bleached hardwood kraft pulp (LBKP, CSF: 360 ml) was added with 0.5% aluminum sulfate based on the total solid content of the pulp slurry, light calcium carbonate (Okutama Kogyo, Tama Pearl TP121-6S, average particle size: 1.8 μm, spindle-shaped light calcium carbonate) and a copolymer to prepare the paper stock. Note that the light calcium carbonate and the copolymer were mixed in a weight ratio of 100:1 to prepare an aqueous slurry, and the slurry was then added to the pulp.

[0095] Using this paper stock as the raw material, a circular hand-made papermaking machine was used to produce a paper with a basis weight of approximately 73 g / m2 in accordance with JIS P 8222. 2 The wet paper after dewatering was dried in a laboratory-scale cylinder dryer instead of the method of contacting the wet paper with a metal plate as specified in JIS P 8222.

[0096] The physical properties of the paper thus produced were evaluated according to the following procedures. (Ash content) Measured according to JIS P8251 (ashing temperature: 525° C.). (Basis Weight) Measured in accordance with JIS P 8124. (Tensile strength) Measured according to JIS P 8113. (Breaking length) Measured according to JIS P 8113

[0097] [Table 2]

[0098] By adding the copolymer according to the present invention, the tear strength index and breaking length increased, and it was confirmed that the decrease in paper strength due to the addition of precipitated calcium carbonate was suppressed. Experiment 3: Production and evaluation of calcium carbonate-loaded paper A pulp slurry consisting of 85% recycled paper pulp (DIP, CSF: 270 ml) and 15% refiner groundwood pulp (RGP, CSF: 110 ml) was mixed with aluminum sulfate at 0.5% and calcium carbonate solids at 7.5% of the total solids in the pulp slurry, and light calcium carbonate (Okutama Kogyo, Tama Pearl TP121-6S, average particle size: 1.8 μm, spindle-shaped light calcium carbonate) and copolymer were added to prepare the stock. Note that the light calcium carbonate and copolymer were mixed in a weight ratio of 100:1 to prepare an aqueous slurry containing the two, and then the slurry was added to the pulp.

[0099] Using this paper stock as the raw material, a circular hand-made papermaking machine was used to produce a paper with a basis weight of approximately 40.5 g / m2 according to JIS P 8222. 2 The wet paper after dewatering was dried in a laboratory-scale cylinder dryer instead of the method of contacting the wet paper with a metal plate as specified in JIS P 8222.

[0100] The physical properties of the paper thus produced were evaluated according to the following procedures. (Basis Weight) Measured in accordance with JIS P 8124. (Paper Thickness) Measured according to JIS P 8118. (Ash content) Measured according to JIS P 8251 (ashing temperature: 525°C). (Opacity) Measured according to JIS P 8149. (Precipitated calcium carbonate on the paper surface) The samples were photographed using an electron microscope, and the amount of precipitated calcium carbonate on the paper surface was evaluated on a five-point scale based on the images (Figures 1 to 3) (5 being the most calcium carbonate and 1 being the least). (Printing evaluation) Using an RI printing machine, two newspaper inks (Vingté en Echo), indigo and red, were printed in layers so that the print density of the printed surface, measured with a Macbeth reflection densitometer, was 1.30. The printed surface was visually evaluated for uneven ink adhesion on a 5-point scale (5 being the least uneven and 1 being the most uneven). For strike-through, only the felt side of the handmade paper was printed, and after conditioning for 24 hours in an environment of 23°C and 50 RH%, the Y value of the wire side (non-printed side) was measured and the strike-through value (%) was calculated using the formula below. Bleed-through (%) = (Y value after printing / Y value before printing) x 100

[0101] [Table 3]

[0102] The paper according to the present invention had good ink adhesion and strike-through when printed. This is thought to be because the light calcium carbonate present near the surface of the paper reduced the penetration of the ink, improving strike-through.

Claims

1. A paper containing a copolymer and precipitated calcium carbonate, the copolymer comprising: (a) a structural unit derived from a monomer represented by the following formula 1: 【Chemistry 1】 [In the formula, R 1 represents an alkenyl group having 2 to 5 carbon atoms; A 1 O may be the same or different and represents an oxyalkylene group having 2 to 18 carbon atoms; n1 represents the average number of moles of the oxyalkylene group added and is a number from 1 to 100; R 2 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms; (b) a structural unit derived from a monomer represented by the following formula 2: 【Chemistry 2】 [In the formula, R 3 , R 4 and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, m represents a number from 0 to 2, A 2 O are the same or different and each represents an oxyalkylene group having 2 to 18 carbon atoms, n2 is the average number of moles of the oxyalkylene group added and is a number from 1 to 100, and X represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms; (c) a structural unit derived from a monomer represented by the following formula 3: 【Chemistry 3】 [In the formula, R 6 , R 7 and R 8 are each independently a hydrogen atom, -CH 3 Or - (CH 2 ) rCOOM 2 represents M 1 and M. 2 are the same or different and each represents a hydrogen atom, an alkali metal, an alkaline earth metal, an ammonium group, an alkylammonium group, or a substituted alkylammonium group; r is an integer of 0 to 2, where -(CH 2 ) rCOOM 2 ,-COOM 1 or other -(CH 2 ) rCOOM 2 When an anhydride is formed, the group M 1 and M. 2 does not exist]; The above paper includes two or more of the above.

2. The paper according to claim 1 , wherein the copolymer is a copolymer containing all of (a) to (c).

3. 3. The paper according to claim 1 or 2, wherein the copolymer has a Mw of 5,000 to 60,000 and a Mw / Mn of 1.0 to 3.

0.

4. The paper according to any one of claims 1 to 3, which is an uncoated paper having an ash content of 3 to 30% by weight.

5. Paper according to any one of claims 1 to 4, containing 0.1 to 10 parts by weight of a copolymer per 100 parts by weight of light calcium carbonate.

6. Paper described in any one of claims 1 to 5, wherein the copolymer is a copolymer containing (b).

7. The paper described in claim 6, wherein the copolymer comprises a constitutional unit derived from a monomer of formula 2 where n2 is 1 and a constitutional unit derived from a monomer of formula 2 where n2 is greater than 1 and less than or equal to 100.

8. A method for producing the paper according to any one of claims 1 to 7, comprising the step of making paper from a stock containing the copolymer, precipitated calcium carbonate and pulp.

Citation Information

Patent Citations

  • Thermal transfer image recording sheet

    JP1990050890A

  • Papermaking method

    JP2012172287A

  • Precipitated calcium carbonate for filler and paper containing the same

    JP2013060692A

  • Coated paper for printing for industrial ink jet printer

    JP2014054832A

  • Copolymer and application of the same

    JP2014125509A